Implementasi Otomoni Khusus Pada Pemerintahan Aceh Dan Papua Dalam Perspektif Perbandingan - Imania Fathu Zahra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Papua gets Special Autonomy based on Law Number 21 of 2001, while Aceh gets Special Autonomy based on Law Number 18 of 2001 an Law Number 2006. This Special Autonomy is a political solution, a legal solution and a solution to achieve prosperity to overcome security problems and demands for separation from the Unitary State of the Republic Of Indonesia (NKRI). This happened when Indonesia was experiencing a vibrant democracy. Legislative Regulations are rules made by the Government. It includes things such as local democracy, people’s welfare and the protection of human rights in our country. The research method used in this research uses the library research method. Literature study is the first step in the information gathering method. From the research conducted, it appears that the Special Autonomy regulations, which are supposed to be responsive in their implementation, are still experiencing many problems. The use and continuation of the Special Autonomy Law still needs to be explained better so that it remins the same and is in line with achieving social happiness.